1991
DOI: 10.1073/pnas.88.2.676
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase A activity of the murine B-lymphocyte differentiation antigen BP-1/6C3.

Abstract: The predicted amino acid sequence of the cDNA encoding the murine B-lymphocyte differentiation antigen BP-1/6C3 suggested that it is a member of the zincdependent metalloprotease family, possibly an aminopeptidase related to aminopeptidase N [microsomal aminopeptidase; a-aminoacyl-peptide hydrolase (microsomal), EC 3. (refs. 4-6; unpublished results).While its broad tissue distribution implied diverse biological function, studies of the BP-1/6C3 antigen thus far have been focused mainly on its possible role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…from the cells subjected to immunoelectrophoretic blot analysis using a polyclonal antibody raised against murine APA [23]. In the crude particulate fraction from cells transfected with wtAPA, APA existing as a disulphide-linked homodimer [7]. In contrast there was no difference in electrophoretic mobility of the C43S mutant under reducing or non-reducing conditions, with the antibody detecting a protein of 147 kDa under both conditions (Figures 2A and 2B, lane 3).…”
Section: Expression and Enzymic Activity Of The Apa Mutantsmentioning
confidence: 88%
See 1 more Smart Citation
“…from the cells subjected to immunoelectrophoretic blot analysis using a polyclonal antibody raised against murine APA [23]. In the crude particulate fraction from cells transfected with wtAPA, APA existing as a disulphide-linked homodimer [7]. In contrast there was no difference in electrophoretic mobility of the C43S mutant under reducing or non-reducing conditions, with the antibody detecting a protein of 147 kDa under both conditions (Figures 2A and 2B, lane 3).…”
Section: Expression and Enzymic Activity Of The Apa Mutantsmentioning
confidence: 88%
“…On the basis of its role in the brain renin-angiotensin system, inhibitors of APA have been reported as potential central antihypertensive agents [5]. APA is identical with the murine B-lymphocyte differentiation antigen BP-1\6C3 and is likely to be involved in early B-cell development [6][7][8]. Plasma APA activity is significantly and consistently lower in Alzheimer's-disease patients than in age-matched controls, and thus the enzyme may have potential use as a diagnostic\predictive marker for this disease [9].…”
Section: Introductionmentioning
confidence: 99%
“…APA has a single transmembrane-spanning domain. 42 APA can be solubilized and retains activity when clipped from the membrane by mild enzymatic digestion, 41 much like what has been shown for ACE. 43 It is not known whether plasma APA is generated in such a fashion or whether it represents a secreted form or some other APA-like enzyme.…”
mentioning
confidence: 99%
“…This motif has been shown to be critical for both zinc binding and catalytic activity in a number of metallopeptidases, including thermolysin, a neutral protease from Bacillus thermoproteolytics, and neutral endopeptidase (11)(12)(13). Enzymatic analysis revealed that the BP-1 antigen exhibited aminopeptidase A (APA) activity (14). In addition, APA activity of a panel of cell lines correlated in a linear fashion with cell surface levels of the BP-1 antigen (14).…”
mentioning
confidence: 99%
“…Enzymatic analysis revealed that the BP-1 antigen exhibited aminopeptidase A (APA) activity (14). In addition, APA activity of a panel of cell lines correlated in a linear fashion with cell surface levels of the BP-1 antigen (14).To obtain direct evidence that BP-1 is APA, we made a full-length BP-1 cDNA clone from two overlapping partial clones. This full-length cDNA was placed downstream from the SRa promoter (15) and expressed in heterologous COS-7 and Ltk-cells.…”
mentioning
confidence: 99%